Patient safety : a human factors approach - Dekker, Sidney, 1969- (Boca Raton : CRC Press, Taylor & Francis Group, 2011)
"With coverage ranging from the influence of professional identity in medicine and problematic nature of "human error", to the psychological and social features that characterize healthcare work, to the safety-critical aspects of interfaces and automation, this book spans the width of the human factors field and its importance for patient safety today. In addition, the book discusses topics such as accountability, just culture, and secondary victimization in the aftermath of adverse events and takes readers to the leading edge of human factors research today: complexity, systems thinking and resilience"--Provided by publisher
Includes bibliographical references and index
Keywords: Patientsäkerhet; Human engineering; Medical errors -- Prevention; Patients -- Safety measures; Professional Competence; Risk Assessment; Safety Management -- methods; Medical Errors -- prevention & control; Patient Care -- methods; safety management; professional competence; medical errors; risk assessment; patient safety